2019
DOI: 10.1177/0310057x19860972
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic benefits of de-escalating stress ulcer prophylaxis therapy in the intensive care unit: A quality improvement study

Abstract: Stress ulcer prophylaxis is commonly prescribed in the intensive care unit but can be inappropriately commenced or continued on discharge, exposing patients to potential harm. We aimed to evaluate whether a prescribing guideline, education program and pharmacist oversight would reduce inappropriate continuation of stress ulcer prophylaxis. This was a multicentre pre- (2014) and post- (2016) quality improvement study across five Australian intensive care units. Cost data were estimated using local information a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(46 citation statements)
references
References 24 publications
1
45
0
Order By: Relevance
“…However, the results illustrated that patients treated with PPIs had a higher risk of nosocomial pneumonia. This is consistent with the findings of Anstey et al 18 The clinical pharmacist intervention targeting the rational use of PPIs did not deteriorate the quality of clinical care. On the contrary, such interventions can prevent the occurrence of adverse drug reactions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the results illustrated that patients treated with PPIs had a higher risk of nosocomial pneumonia. This is consistent with the findings of Anstey et al 18 The clinical pharmacist intervention targeting the rational use of PPIs did not deteriorate the quality of clinical care. On the contrary, such interventions can prevent the occurrence of adverse drug reactions.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have demonstrated that clinical pharmacist interventions have a significant role in the rational use and costs of PPIs 17‐23 . To date, little research has examined the effects of clinical pharmacist interventions on PPI use in hepatobiliary surgery wards.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…We included 8 studies from 9 articles in the narrative synthesis. [14,[23][24][25][26][27][28][29][30] All studies were cohort studies, of which 6 (75.0%) were retrospective and the other 2 (25.0%) were prospective.…”
Section: Study Selectionmentioning
confidence: 99%
“…Four (50%) studies clari ed the indication for the initiation and discontinuation of SUP pharmacotherapy by developing locally SUP pharmacotherapy guidelines/protocol or algorithm. [14,23,27,29] Four (50%) studies provided the medical staff with an educational intervention and/or supplied a pocket card of SUP pharmacotherapy indications for reference. [24,25,27,28] In 3 (37.5%) studies, pharmacists reviewed each patient on SUP pharmacotherapy during medical ICU rounds.…”
Section: Intervention Content and Deliverymentioning
confidence: 99%
See 1 more Smart Citation